2000
DOI: 10.1260/0263617001493558
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Kinetic Characteristics of HSA Adsorption by Different Types of Activated Carbon Fibres

Abstract: Adsorption of human serum albumin (HSA) from aqueous solution on to activated carbon fibres (ACF) with different degrees of activation in the range 0-70% has been studied at 293 ± 1K. The various parameters for the porous structure were calculated by different methods on the basis of the low-temperature adsorption isotherms of nitrogen measured at 77 ± 1 K. It was shown that an increase in the degree of ACF activation led to the development of a porous structure which exhibited increasing values of the micropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…First, L. variegatus may be affected by CM‐enriched sediment because of the chemistry of CM (taste, smell, composition) 51, 82, because it has been shown that even 1% carbon amendment can affect the feeding activity of L. variegatus 93. Another explanation may relate to the surface reactivity of CM, with its high affinity for lipids, carbohydrates, and proteins 94, 95. Possibly CM sorb nutrients that serve as a food source for worms or impair digestion processes 52, 82, but no statistically or biologically relevant effect of AC has been found on enzyme activity or digestive fluid surfactance in AC‐amended sediment 52.…”
Section: Effects Of CM On Benthic Species and Communitiesmentioning
confidence: 99%
“…First, L. variegatus may be affected by CM‐enriched sediment because of the chemistry of CM (taste, smell, composition) 51, 82, because it has been shown that even 1% carbon amendment can affect the feeding activity of L. variegatus 93. Another explanation may relate to the surface reactivity of CM, with its high affinity for lipids, carbohydrates, and proteins 94, 95. Possibly CM sorb nutrients that serve as a food source for worms or impair digestion processes 52, 82, but no statistically or biologically relevant effect of AC has been found on enzyme activity or digestive fluid surfactance in AC‐amended sediment 52.…”
Section: Effects Of CM On Benthic Species and Communitiesmentioning
confidence: 99%
“…During our sediment exposure trials, we observed ingestion of activated carbon particles by N. arenaceodentata, but not L. plumulosus, and it is conceivable that ingested activated carbon affects N. arenaceodentata indirectly because of its sorbent properties. Given its affinity for lipids, carbohydrates (38), and proteins (39), activated carbon could sorb nutrients dissolved in both the aqueous phase and digestive fluid, potentially impairing nutrient uptake. In addition, since the species was observed to ingest activated carbon particles, it is possible that activated carbon might impair digestion through the sorption of enzymes in digestive fluid.…”
Section: Bsaf )mentioning
confidence: 99%
“…The presence of black carbon also had effects on the biomass and lipid content of L. variegatus (Supplemental Data, Figures S3 and S4). It has been reported that strong sorbents, such as activated carbon, can sequester lipids, carbohydrates, and proteins, which represent essential nutrients for organisms (Eretsky ). Hence, the lower biomass and lipid content in L. variegatus in the black carbon–amended sediments were likely attributable to the sequestration of nutrients by the black carbon amendments.…”
Section: Discussionmentioning
confidence: 99%